(3OhQ GdgjFI GdYGeI dShb GdeGd ai MeGjI CbdjI GdeSGgejf ai GdTQcGJ GdeSGgeI (B: s (3OQGSI ebGQfI ai GdfXGejf GdSYhOj hGdeUQj (B/ s - (3eMeO YWG Gddg Ydj GdeGVj s; (3SejMI GdbdjhHjs; (3eMehO eNJGQ HQjQjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2009)
(3dbO JfGhd ehVhY OhQ GdgjFI GdYGeI dShb GdeGd ai MeGjI CbdjI GdeSGgejf ai GdTQcGJ GdeSGgeI ai GdbGfhf GdeUQi hGdSYhOi hPdc HgOa GSJLdGA eXGgQ Jdc GdMeGjI ai GdbGfhfjf eMd GdebGQfI hbO LGAJ gPg GdOQGSI ai aUdjf QFjSjjf jSHbgeG aUd JegjOi hHeG Cf eMhQ GdOQGSI jbhe Mhd OhQ gjFI Shb GdeGd ai MeGjI GdCbdjI acGf dGHO ef GdJYQV dgjFI Shb GdeGd ef MjK JchjfgG hWQjbI JTcjdgG s
(3CWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdJLGQj (B2009.s
(3HHdjhLQGajG(B: (3UaMGJ (B251-260.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3eUQs -- (3Shb GdeGds; (3GdSYhOjIs -- (3Shb GdeGds; (3JOGhd GdCSges; (3Shb GdeGd GdSYhOj s; (3Shb GdeGd GdeUQj s; (3GdJaJjT Ydi TQcGJ GdeSGgeIs; (3eQGbH GdMSGHGJs; (3OYhi GdeSGge GdaQOjIs; (3GdJYSas; (3GdEaUGM hGdTaGajIs; (3GdeeGQSGJ ZjQ GdeTQhYIs; (3SdWGJ eLdS GdGOGQIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQj s